2021
DOI: 10.1108/bfj-09-2020-0785
|View full text |Cite
|
Sign up to set email alerts
|

Modified atmosphere packaging for milk cake: assessment of ideal gas composition for extending shelf life

Abstract: PurposeMilk cake is a well-renowned khoa-based dairy product in India, produced either from the buffalo milk or using a specific danedar variety of khoa. Under ambient conditions, shelf-life of milk cake is generally up to 3–4 days, whereas under refrigeration conditions, it can last up to 12–14 days. Therefore, the present study aims to evaluate the effect of modified atmosphere packaging (MAP) to enhance the shelf-life and keeping intact freshness of milk cake under refrigerated conditions (4 ± 2 °C).Design/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 20 publications
0
3
0
2
Order By: Relevance
“…Aktif maddeler, hem gıda kalitesini hem de ürün raf ömrünü arttırmaktadır. Bunların arasında, antimikrobiyal ajanların biyopolimer bazlı yenilebilir filmlere dahil edilmesi, aktif gıda paketleme teknolojisindeki önemli gelişmelerden biridir [20]. Bu şekilde paketlemenin, gıda kontaminasyonuna neden olan patojenik / bozucu ögeleri önlemede veya öldürmede son derece etkili olduğu görülmüştür.…”
Section: Yeni̇lebi̇li̇r Fi̇lm Ambalajlamaunclassified
See 1 more Smart Citation
“…Aktif maddeler, hem gıda kalitesini hem de ürün raf ömrünü arttırmaktadır. Bunların arasında, antimikrobiyal ajanların biyopolimer bazlı yenilebilir filmlere dahil edilmesi, aktif gıda paketleme teknolojisindeki önemli gelişmelerden biridir [20]. Bu şekilde paketlemenin, gıda kontaminasyonuna neden olan patojenik / bozucu ögeleri önlemede veya öldürmede son derece etkili olduğu görülmüştür.…”
Section: Yeni̇lebi̇li̇r Fi̇lm Ambalajlamaunclassified
“…Antimikrobiyal ajanların ambalaj malzemelerine eklenmesi, antimikrobiyal aktivitelerinde mutlak uyumsuzluğa neden olabilir. Bu nedenle, gıdaya özgü doğru antimikrobiyal ajanı ve hedef organizmalara karşı minimum inhibitör konsantrasyonu dikkate alınarak düzeltilmiş miktarda bir paketin seçilmesi önemlidir [20] Nanoteknoloji, gıda güvenliği ve gıda sürdürülebilirliğindeki mevcut zorluklar için yeni bir anahtar iyileştirme kaynağı gibi görünüyor. Nanoteknoloji kavramı, 1959'da Richard Feynman tarafından tanıtılmıştır [23].…”
Section: Yeni̇lebi̇li̇r Fi̇lm Ambalajlamaunclassified
“…This concept can also be called the principle of food preservation so that the shelf-life is longer 47) . Until now, some studies have reported the applications of MAP technology, including fresh fruit and vegetable products 48,49) , fresh meat and processed meat products [50][51][52][53] , mushrooms 54,55) , fish and shellfish products 56,57) , cheese 46,58,59) , bread and cake 60,61) , and herbs and spices 62,63) . Indonesia is rich in natural resources 64) in agriculture, plantations, animal husbandry, and fisheries.…”
Section: Introductionmentioning
confidence: 99%
“…Market intelligence companies have predicted that by the year 2025, the smart food packaging market is going to dominate North America followed by Europe and the Asia Pacific region, while by the year 2026, the MAP market is projected to reach US $ 18.51 billion with a CAGR of about 6.2% [ 1 , 2 ]. In MAP, the gas composition in the headspace of a food package is changed in such a way that it leads to extended shelf life by reducing microbial growth and chemical deterioration reaction [ 3 ]. IP contains external or internal indicators that portray historical information of the package along with or without the quality of the food.…”
Section: Introductionmentioning
confidence: 99%